Metformin and Polycystic Ovary Syndrome - Omran, Maha Yousef Soliman (Qassim University, Kingdom of Saudi Arabia, 2007)
The polycystic ovary syndrome (PCOS), one of the most common causes of infertility due to anovulation, affects 4–7% of women). Etiology of PCOS remains largely unknown, familial aggregation of cases suggests genetic susceptibility to the disorder. Though genes involved remain unknown, recent evidence points to a gene of the insulin receptor. Genes implicated in ovarian follicular development may also play a role. A fundamental aspect of the syndrome seems to be a defect in insulin metabolism. There is consistent evidence that increase of body weight may favour a more severe hyperandrogenism. Treatment of PCOS has been mostly symptomatic. Only recently has the use of insulinomimetic or insulin sensitizing agents provided an option to treat the presumed underlying cause of this disorder, which is insulin resistance. Metformin appears to improve risk factors for cardiovascular disease in diabetic and non-diabetic patients, indicating that its use could be associated with a reduction in coronary heart disease in patients with PCOS. The use of metformin in hyperinsulinemic women with PCOS improved the lipid profile, including decreases in total cholesterol, low density lipoprotein cholesterol, and triglyceride concentration.